(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Darunak is a Vata –Kaphaj Vyadhi. Sushruta mentioned it under Kshudra roga. Chakradatta has mentioned application of Maltyadi Tail (Jaati, Karveer, Chitrak, Karanj, base oil- Tila Tail) in the treatment of Darunak. Aggravation of Kapha and Vata in Darunak causes, itching, falling of hair, loss of sensation, dryness and small cracks of the skin of the scalp. Several factors increase the risk of developing dandruff, including a person’s age, the weather, stress levels, fungus, medical conditions, and choice of hair products. Oiling is the best way to get a healthy scalp. Aim and objective: To evaluate efficacy of Maltyadi Tail in the management of Darunak w.s.r to dandruff. Materials and Methods: In this clinical study total 46 Patients of Darunak were registered out of which 3 patients left the treatment; remaining 43 patients were divided into 2 groups. 23 patients were treated in group A (test drug- Maltyadi Tail) and 20 patients were treated in group B (control drug- Tila Tail) for 30 days. The effect of therapy was assessed on the basis of changes in grading score. Result: In clinical study, All the cardinal and associate symptoms except Raag, Daah, Ruja were statistically significant improved after the complete course of test drug (Maltyadi Tail). Effect of Group A reduced Kesha Bhoomi Rookshta by 92.68%, Kandu by 100%, Keshbhoomi Prapatan by 92.68% and Keshchyuti by 87.50% which was statistically highly significant. Conclusion: The study revealed that test drug (Maltyadi tail) is more effective in Darunak /dandruff compare to control drug (Tila Tail).